Upper cervical range of motion is impaired in patients with painful temporomandibular disorders - Grondin, F.; Hall, Toby; Laurentoye, M.; Ella, B. (Maney Publishing, 2014)
Aims: Clinicians increasingly suggest assessment and treatment of the cervical spine in patients with temporomandibular dysfunction (TMD); however, few studies have investigated upper cervical spine mobility in people who suffer from TMD. The purpose of this study was to investigate whether patients with TMD pain (with or without headache) present with upper cervical spine impairment when compared with asymptomatic subjects. Methodology: A single blind examiner evaluated cervical range of motion (ROM) measures including axial rotation during the flexion–rotation test (FRT) and sagittal plane ROM. Twenty asymptomatic subjects were compared with 37 subjects with pain attributed to TMD, confirmed by the Revised Research Diagnostic Criteria. Subjects with TMD were divided according to the presence of headache (26 without headache TMDNHA, 11 with headache TMDHA). One-way analysis of variance and planned orthogonal comparisons were used to determine differences in cervical mobility between groups. All subjects with TMD were positive on the FRT with restricted ROM, while none were in the control group. Results: The analysis of variance revealed significant differences between groups for the FRT F(2,54) = 57•96, P<0•001) and for sagittal ROM [F(2,54) = 5•69, P = 0•006]. Findings show that the TMDHA group had less axial rotation than group TMDNHA, and both TMD groups had less ROM than controls. For sagittal ROM, the only difference was between group TMDHA and controls. Conclusions: Subjects with TMD had signs of upper cervical spine movement impairment, greater in those with headache. Only subjects with TMD and headache had impairment of cervical spine sagittal plane mobility. This study provides evidence for the importance of examination of upper cervical mobility determined by the FRT in patients who suffer from TMD.